Ecosystems in public service logic literature - Rossi, Paula (Routledge, 2025)
The purpose of the chapter is twofold. First, the scholarly work addressing the Public Service Ecosystem (PSE) framework in the Public Service Logic (PSL) literature is explored in order to understand how and why the PSE framework is being utilized. Second, the analysis is then used to further develop the theorizations of PSL as well as to provide pathways for future empirical research.
Keywords: public service logic; public service ecosystem; public management; public services; fi=Julkisjohtaminen|en=Public Management|